2009
DOI: 10.1038/embor.2009.224
|View full text |Cite
|
Sign up to set email alerts
|

Protein quality control—linking the unfolded protein response to disease

Abstract: The proper folding of proteins is essential for cellular homeostasis and prevention of an ever‐growing number of diseases. Here, the authors highlight recent breakthroughs in the study of the unfolded protein response and new strategies to combat the diseases caused by its malfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…1 ) may be because of (i) differential protein vs. RNA turnover, (ii) no rate-limitation of mRNA levels with regard to protein synthesis, (iii) these proteins are part of multigene family, while antibody recognizes shared epitopes, or (iv) species differences as antibodies were raised against and validated for human, not Chinese hamster antigens. Interestingly, we found substantial upregulation of BiP, the ER UPR stress sensor, 34 which showed nuclear and cytoplasmic localization in A23 CBS I278T or R125Q cells compared to weak nuclear localization in A23 CBS WT cells ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…1 ) may be because of (i) differential protein vs. RNA turnover, (ii) no rate-limitation of mRNA levels with regard to protein synthesis, (iii) these proteins are part of multigene family, while antibody recognizes shared epitopes, or (iv) species differences as antibodies were raised against and validated for human, not Chinese hamster antigens. Interestingly, we found substantial upregulation of BiP, the ER UPR stress sensor, 34 which showed nuclear and cytoplasmic localization in A23 CBS I278T or R125Q cells compared to weak nuclear localization in A23 CBS WT cells ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 84%
“…BiP upregulation may actually represent cellular compensatory action to prevent UPR, because BiP acts as a suppressor of double‑stranded RNA‑dependent protein kinase‑like ER (PERK), activating transcription factor 6 (ATF6) and inositol‑requiring enzyme 1 (IRE1) signaling pathways. 34 …”
Section: Discussionmentioning
confidence: 99%
“…Utilization of these two alternative pathways to dispose of pathogenic CBS variants may potentially be related to the induction of ER stress due to CBS misfolding and aggregation (or formation of higher‐molecular weight complexes). Previously we showed that the expression of CBS I278T variant significantly upregulates expression of several cytoplasmic molecular chaperones and substantially increases the expression of BiP, an ER sensor of unfolded protein response (Collard & Majtan, 2023 ; Cyr & Hebert, 2009 ) indicating involvement of ER in proteostasis of HCU CBS variants. ALP is the second main pathway for protein degradation after UPS, typically used for protein aggregates and organelles (Siva Sankar & Dengjel, 2020 ).…”
Section: Discussionmentioning
confidence: 96%